[Rezension von: Öhrström, Lars, The last alchemist in Paris] - Linti, Gerald W. (Angewandte Chemie. International edition, 2014)
Oxford University Press, Oxford, 2013. 272 pp., hardcover, £ 16.99.—ISBN 978-0199661091
Gesehen am 07.12.2020
Keywords: Rezension